If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(g+3)=-10
We move all terms to the left:
-4(g+3)-(-10)=0
We add all the numbers together, and all the variables
-4(g+3)+10=0
We multiply parentheses
-4g-12+10=0
We add all the numbers together, and all the variables
-4g-2=0
We move all terms containing g to the left, all other terms to the right
-4g=2
g=2/-4
g=-1/2
| 10-5(2x-9)=-(-2x+10)+5 | | 7/3x+3=1/3+1/3x | | 4y-(-16)=-12 | | 7/10=v/30 | | 84=51-14c | | 4x+81/5=15 | | -1/3x=-1/4x-1 | | 8*(5*2)=(8*n)*2 | | 9^x-6(3^x)+8=0 | | (5.4)/(2y)=9 | | 9a-7a=27 | | -1+8y=-10 | | 23-5z=3(z-3) | | x2–10=30x | | 12+4(3x+2)=-16 | | 32.5+2y=9y+15 | | 7*12=5p | | 7(x-19=3•7 | | 2x-19=3x-12 | | 4(a+1=2 | | 5w+14=6w+19 | | 6v+15=2v+31 | | 2s-7-8=-17 | | 2÷5+m=5÷6 | | 4u+12=7u-12 | | -62x+18=0 | | 1/2n-9=1+-1/8n | | 18x+5=4x+145 | | 24v=100 | | -3=2x−10 | | 3/4w6=9-1/4w | | 4x^2-44x-36=0 |